Pendekatan Metode User-Centered Design dan System Usability Scale dalam Redesain dan Evaluasi Antarmuka Website - Migunani Puspita Eugenia; Muhammad Abdurrofi; Bagus Almahenzar; Ardita Khoirunnisa (Politeknik Statistika STIS, 2022)
The agricultural census dissemination website is one of the media created by BPS to publish the results of agricultural censuses in Indonesia. The last update of the agricultural census dissemination website was carried out in 2013 so that an update was needed related to the usefulness of the system and other features that were considered less relevant to the times. The website redesign process uses a user-centered design (UCD) approach with evaluation using a system usability scale (SUS) questionnaire. The initial evaluation questionnaire was distributed to 50 respondents consisting of various user groups, namely the ST secretariat, BPS employees, lecturers, students, and the general public. The purpose of this study is to determine the redesign and evaluation of the website interface for the dissemination of the agricultural census. Based on the initial evaluation, the SUS score obtained was 60.05 points. After the redesign, the final results of the evaluation obtained showed that the design of the solution resulting from the redesign of the system using the UCD approach was better than the initial design of the system.